Advances in applied biotechnology : proceedings of the 3rd International Conference on Applied Biotechnology (ICAB2016), November 25-27, 2016, Tianjin, China /: proceedings of the 3rd International Conference on Applied Biotechnology (ICAB2016), November 25-27, 2016, Tianjin, China. ([2018]) - Unknown
No abstract available